2021
DOI: 10.1123/ijspp.2019-0861
|View full text |Cite
|
Sign up to set email alerts
|

The Anthropometric, Physiological, and Strength-Related Determinants of Handcycling 15-km Time-Trial Performance

Abstract: Purpose: The aim of this study was to investigate the relationship between selected anthropometric, physiological, and upper-body strength measures and 15-km handcycling time-trial (TT) performance. Methods: Thirteen trained H3/H4 male handcyclists performed a 15-km TT, graded exercise test, 15-second all-out sprint, and 1-repetition-maximum assessment of bench press and prone bench pull strength. Relationship between all variables was assessed using a Pearson correlation coefficient matrix with mean TT veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…5 Researchers have employed in/outdoor TTs to simulate competitive events. 26,[28][29][30]32,33 During an outdoor 22-km TT, average speeds of 29.3 to 30.4 km•h −1 ; VO 2 , 28.5 to 30.7 mL•kg −1 •min −1 (82%−89% VO 2 peak); HR, 166 to 172 bpm; and respiratory exchange ratio, 1.03 to 1.14, were reported in H3 athletes. 26 Using H1 to H5 participants, Flueck et al, 30 demonstrated laboratorybased 10 km TT times of 18.4 (4.1) minutes, average power output (PO) of 142 (49) (∼80% PO peak ), and average HR responses of 162 (27) bpm; however, information relating to performance differences between athlete classifications was not reported.…”
Section: Physiology Of Handcyclingmentioning
confidence: 98%
See 4 more Smart Citations
“…5 Researchers have employed in/outdoor TTs to simulate competitive events. 26,[28][29][30]32,33 During an outdoor 22-km TT, average speeds of 29.3 to 30.4 km•h −1 ; VO 2 , 28.5 to 30.7 mL•kg −1 •min −1 (82%−89% VO 2 peak); HR, 166 to 172 bpm; and respiratory exchange ratio, 1.03 to 1.14, were reported in H3 athletes. 26 Using H1 to H5 participants, Flueck et al, 30 demonstrated laboratorybased 10 km TT times of 18.4 (4.1) minutes, average power output (PO) of 142 (49) (∼80% PO peak ), and average HR responses of 162 (27) bpm; however, information relating to performance differences between athlete classifications was not reported.…”
Section: Physiology Of Handcyclingmentioning
confidence: 98%
“…21,32 Indeed, PO 4 was shown to be the strongest predictor of performance in a simulated 16 km TT accounting for 59.3% of total variance. 33 More recently, Nevin and Smith, 33 demonstrated very large correlations between 15-km TT velocity and measures of PO 4 , VO 2 peak (in milliliter per kilogram per minute), PO peak (in Watts per kilogram), body mass, and maximal anaerobic power. In the context of performance determinants, recent findings have also pointed to the importance of absolute and relative values of upper body strength.…”
Section: Physiology Of Handcyclingmentioning
confidence: 99%
See 3 more Smart Citations